Syiar Digital Melalui Pelayanan Publik: Peran Sistem Informasi dalam Membangun Citra Birokrasi Islami di BDK Medan - Tala, Sultan; Buyung, adnan; mailin, Mailin (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2026)
Digitalization in the public sector is no longer merely a technological upgrade but a strategic instrument for conducting digital syiar (propagation) through transparent and accountable services. This study aims to analyze the role of information systems at the Medan Religious Education and Training Center (BDK Medan) as a medium for building an Islamic bureaucratic image aligned with da'wah values. The primary background of this research is the inefficiency found in conventional administrative systems, such as data redundancy and organizational communication barriers that hinder public service delivery. Using a descriptive qualitative method, data were collected through participatory observation during Field Work Practice (PKL), in-depth interviews, and documentation studies. The results indicate that the implementation of information systems at BDK Medan represents a concrete form of da'wah bil-hal (propagation through action), where the values of amanah (trustworthiness), shidiq (honesty), and fastabiqul khairat (competing in goodness) are integrated into the digital service workflow. The digitalization of registration processes, centralized database management (single source of truth), and the issuance of e-certificates equipped with QR Codes have effectively minimized human error, trimmed layered bureaucracy, and created accountability through the provision of digital audit trails. Despite facing challenges such as digital literacy gaps and network stability issues, BDK Medan has implemented adaptive communication strategies and assistance (mu'awanah) for users. Ultimately, this information system has transformed into a modern syiar medium representing bureaucratic professionalism under the Ministry of Religious Affairs while building an institutional image that is superior, dignified, and responsive to the needs of the community